No More Nagasakis Interfaith Action toward a World without Nuclear Weapons - Ihara, Toyokazu (Cornell University Press, 2019)
In a speech delivered in Japanese at Cornell University, atomic bomb survivor Tomokazu Ihara describes the bombing of his home city of Nagasaki in 1945, traces his activism against nuclear proliferation, and issues an impassioned plea for a world without nuclear weapons. Cornell Global Perspectives is an imprint of Cornell University's Mario Einaudi Center for International Studies. The works examine critical global challenges, often from an interdisciplinary perspective, and are intended for a non-specialist audience. The Distinguished Speaker Series presents edited transcripts of talks delivered at Cornell, both in the original language and in translation.